Controlled temperature contrasts of three native and one highly invasive annual plant species in California - Mario Zuliani; Stephanie Haas-Desmarais; Laura Brussa; Jessica Cunsolo; Angela Zuliani; Christopher J. Lortie (PeerJ)
Plant responses to changes in temperature can be a key factor in predicting the presence and managing invasive plant species while conserving resident native plant species in dryland ecosystems. Climate can influence germination, establishment, and seedling biomass of both native and invasive plant species. We tested the hypothesis that common and widely distributed native and an invasive plant species in dryland ecosystems in California respond differently to increasing temperatures. To test this, we examined the effects of temperature variation on germination, establishment, and per capita seedling biomass of three native and one invasive plant species (Bromus rubens) in independent 6 week growth trial experiments in a controlled greenhouse. Higher relative temperatures reduced the germination and establishment of the tested invasive species and two tested native species, however, per capita biomass was not significantly affected. Specifically, germination and establishment of the invasive species B. rubens and the native species Phacelia tanacetifolia was significantly reduced. This invasive species can often outcompete natives, but increasing temperature could potentially shift the balance between the germination and establishment of natives. A warming climate will likely have negative impacts on native annual plant species in California tested here because increasing temperatures can co-occur with drought. This study shows that our tested native annual plant species tested here have some resilience to relatively significant increases in temperature, and this can favor at least one native species relative to at least one highly noxious invasive plant species.